PENERAPAN TEKNOLOGI PESTISIDA NABATI PADA BUDIDAYA PADI DAN CABAI DI NAGARI CAMPAGO KECAMATAN LIMAKOTO KAMPUNG DALAM KABUPATEN PADANG PARIAMAN - Aprizal Zainal; Silvia Permata S; Musliar Kasim; Auzar Syarif; Gustian Gustian; Benni Satria; Netti Herawati (Jurnal Hilirisasi IPTEKS, 2022)
Nagari Campago is located in Limakoto Subdistrict, Kampung Dalam, Padang Pariaman Regency. The area has great potential in agriculture, because there is a large area of wetland agriculture for white rice cultivation and dry land for chili plants and other seasonal crops. However, the reality that happened to Nagari Campago was that several times the harvest period, farmers experienced pests and diseases that resulted in crop failure. Farmers have limited information on red rice cultivation. The purpose of this activity is for Nagari Campago farmers to gain knowledge and understanding about brown rice, farmers can recognize and be able to make vegetable pesticides that can be used to control plant pests and diseases, thereby reducing maintenance costs. This activity was carried out in Nagari Campago, Limokoto Subdistrict, Kampung Dalam, Padang Pariaman Regency, West Sumatra Province. The method used is lecture, demonstration, discussion, monitoring. Socialization of the benefits of brown rice and demonstration training on the manufacture of vegetable pesticides to partners of the “Bukik Caliak Indah” farmer group. The result of the implementation of the activity is that the community is very interested in the cultivation of organic red rice and chili. The community is able to make their own botanical pesticides to control plant pests and diseases. From the results of the activity, it can be concluded that farmers are aware of environmentally friendly cultivation, and alternative sources of food crops.